2021
DOI: 10.1177/08971900211038864
|View full text |Cite
|
Sign up to set email alerts
|

Variation Among Infectious Diseases Pharmacists for the Treatment of Staphylococcus aureus Bacteremia

Abstract: Introduction Staphylococcus aureus bacteremia (SAB) remains complex, in that optimal treatment for patients, including complicated or persistent infection, remains unclear. Two recent surveys have demonstrated practice variations in SAB among infectious diseases (ID) physicians. Objectives The purpose of this survey was to examine practice variations in SAB among ID pharmacists. Methods A thirty-five-question survey was electronically distributed to the American College of Clinical Pharmacy (ACCP) Infectious D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our study is not without limitations. Our sample size ( n = 68) was smaller than other previous surveys of the ACCP ID PRN, 17 but similar in size to a survey of the ACCP ID PRN on outpatient parenteral antimicrobial therapy (OPAT) ( n = 87). 36 With the majority of respondents in our survey having 10 years or less of practice, it may have led to bias.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our study is not without limitations. Our sample size ( n = 68) was smaller than other previous surveys of the ACCP ID PRN, 17 but similar in size to a survey of the ACCP ID PRN on outpatient parenteral antimicrobial therapy (OPAT) ( n = 87). 36 With the majority of respondents in our survey having 10 years or less of practice, it may have led to bias.…”
Section: Discussionmentioning
confidence: 85%
“…The methods were similar to our previous survey on SAB. 17 All authors had previous experience with survey development. The authors developed the survey to focus on unanswered questions or topics surrounding VRE BSI based on a recent review of the literature for VRE BSI that demonstrated mortality advantages with daptomycin therapy, highlighted the uncertainties of managing daptomycin non-susceptible VRE BSI, and questioned the role of combination therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators required infectious diseases consultations for all patients, which has been shown to decrease mortality in SAB, but is mandatory in only 28% of hospitals. 71,72 In addition, only 36% of patients were bacteremic at the time of enrollment. These observations likely explain the lower overall 12-week all-cause mortality of 15% when compared with a 90-day all-cause mortality of 26% observed from the large prospective US cohort.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…In some way, the coronavirus disease 2019 pandemic has highlighted the global societal value of RDTs and raised awareness of the importance of diagnostic capabilities [ 6 8 ]. However, global use of RDTs as part of antimicrobial stewardship programmes (ASPs) remains low [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%